Allelopathic Potential of Medicinal Plants: Costus speciosus Koen ex. Retz and Justicia adhatoda Linn - Devkota, Anjana; Sharma, Swasti (Journal of Natural History Museum, 2015)
The study was carried out to evaluate the allelopathic effect of aqueous extract of rhizome and leaves of Costus speciosus Koen ex. Retz and Justicia adhatoda Linn. respectively on germination and growth of wheat (Triticum aestivum Linn.) and pea (Pisum sativum Linn.). Effect was assessed by recording their effects on germination and percentage growth of root and hypocotyle of test plants. However, the extent of inhibitory and stimulatory effect of extracts varied with the plant species. The extract reduced the germination of the test seeds. However, root and hypocotyle elongations of wheat and pea seedlings were significantly inhibited by the extract of studied plant parts, with the percentage of inhibition increased as the concentration of the extract increased. The observed allelopathic activity of the extract of both medicinal plants on the seed germination and seedling growth of wheat and pea was attributed to the presence of the allelopathic phytochemicals in medicinal plants. The results showed that Justicia adhatoda Linn. had strong inhibitory effect on germination as well as root and hypocotyls growth of test seeds. Phytochemical screening of both medicinal plants was also carried out by using standard methods. The extract contained alkaloid, terpenoids, flavonoids, tannins and saponins in different proportions; with more of alkaloids, flavonoids and terpenoids. J. Nat. Hist. Mus. Vol. 28, 2014: 57-65